Immunotherapy versus lenvatinib in hepatocellular carcinoma: the need for granular data and prospective validation - Ming Zhao; Song Chen; Qi-Feng Chen; Xiong-Ying Jiang (Journal for ImmunoTherapy of Cancer)
Hepatocellular carcinoma (HCC) remains a leading cause of cancer-related mortality worldwide, with systemic therapies constituting the cornerstone of treatment for advanced-stage disease. While lenvatinib has been a widely used first-line agent, the advent of immunotherapy—particularly combinations such as atezolizumab-bevacizumab and the durvalumab plus tremelimumab (STRIDE regimen)—has redefined the therapeutic landscape. Recent retrospective and real-world studies have yielded conflicting results regarding the comparative effectiveness of lenvatinib and immunotherapy. Rimini et al noted a survival benefit for lenvatinib in HCC, though real-world studies meta-analysis showed similar survival outcomes to atezolizumab-bevacizumab, while Ahn et al, via target trial emulation, reported better outcomes with immunotherapy. However, limitations such as lack of key clinical variables, heterogeneous treatment regimens, and residual confounding complicate interpretation. These findings highlight the need for prospective, etiology-stratified research with comprehensive clinical data to optimize first-line therapy selection and inform personalized treatment strategies in advanced HCC.